Correlation between Nasal Patency and Chronic Rhinosinusitis based on Peak Nasal Inspiratory Flow and Sino-Nasal Outcome Test-22 - Hendradewi, Sarwastuti (Indonesian Basic and Experimental Health Sciences, 2024)
INTRODUCTION Chronic Rhinosinusitis (CRS) is a chronic inflammatory condition of the sinuses and nasal mucosa that affects quality of life. This study aims to analyze the correlation between Peak Nasal Inspiratory Flow (PNIF) and Sino-Nasal Outcome Test-22 (SNOT-22) in assessing nasal patency in CRS patients. METHODS This study used a cross-sectional design with CRS patient subjects who underwent PNIF examination and were interviewed using SNOT-22. Statistical analysis involved normality test, log transformation, and Mann Whitney test for non-normally distributed data. RESULTS Results showed that there was a significant correlation between increased PNIF scores and decreased SNOT-22 scores (p=0.021), indicating improved nasal patency and decreased CRS symptoms. The data showed a significant difference between the groups with normal and low PNIF in terms of SNOT-22 scores. In normal PNIF there were 6 people with Mild SNOT-22 and 1 person with M-S SNOT-22. In low PNIF there were 2 people with Mild SNOT-22 and 44 people with M-S SNOT-22. CONCLUSION PNIF and SNOT-22 are effective as measurement tools to assess nasal patency in CRS patients. The correlation between these two tools shows that increased nasal patency is associated with decreased CRS symptoms.